Strategi Dekarbonisasi Untuk Industri Pertambangan Batu Bara di Indonesia Menggunakan Metode TOPSIS - Alam, Huud; Reza, Muhammad (Politeknik ATI Padang, 2024)
The coal mining industry is one of the largest contributors to Indonesia’s economy and greenhouse gas emissions at the same time. Indonesian coal mining companies will inevitably expand their business to meet the demand and targets. But Indonesia already set its ambition to become a net-zero country by 2060 or earlier. Without a robust decarbonization strategy at the company level, Indonesia will face difficulties meeting the net-zero target. This study proposes to use one of the Multi-Criteria Decision Analysis, Technique for Order of Preference by Similarity to Ideal, Solution method within the Political, Economic, Social, Technology, Environmental, and Legal criteria to assess five prioritized decarbonization strategies, which are renewable energy, equipment electrification, business shifting, process efficiency, carbon offset. The analysis will evaluate essential sub-criteria such as regulation compliance, investment, social acceptance, technological readiness, and emissions reduction. The data was acquired from a survey of coal mining stakeholders, other journal reviews, and company disclosures. The final results show that process efficiency scores highest on the selected criteria due to high economic and technological value. Meanwhile, other criteria like carbon offset, renewable energy use, and equipment electrification receive lower scores.